Encapsulation of biocides by cyclodextrins: toward synergistic effects against pathogens - Nardello-Rataj, Véronique; Leclercq, Loïc (Beilstein Journal of Organic Chemistry, 2014)
Host–guest chemistry is useful for the construction of nanosized objects. Some of the widely used hosts are probably the cyclodextrins (CDs). CDs can form water-soluble complexes with numerous hydrophobic compounds. They have been widespread used in medicine, drug delivery and are of interest for the biocides encapsulation. Indeed, this enables the development of more or less complex systems that release antimicrobial agents with time. In this paper, the general features of CDs and their applications in the field of biocides have been reviewed. As the key point is the formation of biocide–CD inclusion complexes, this review deals with this in depth and the advantages of biocide encapsulation are highlighted throughout several examples from the literature. Finally, some future directions of investigation have been proposed. We hope that scientists studying biocide applications receive inspiration from this review to exploit the opportunities offered by CDs in their respective research areas.
Keywords: cyclodextrin; biocide; encapsulation; host–guest chemistry; pathogen; textile

Cyclodextrin technology - Szejtli, J. (Kluwer Academic Publishers, 1988)

(untitled) - Saenger, W.; Jacob, J.; Gessler, K.; Steiner, T.; Hoffmann, D.; Sanbe, H.; Koizumi, K.; Smith, S. M.; Takaha, T. (Chem. Rev., 1998)

(untitled) - Rekharsky, M. V.; Inoue, Y. (Chem. Rev., 1998)

(untitled) - Uekama, K.; Hirayama, F.; Irie, T. (Chem. Rev., 1998)

(untitled) - Noujeim, N.; Leclercq, L.; Schmitzer, A. R. (Curr. Org. Chem., 2010)

(untitled) - Harata, K. (Chem. Rev., 1998)

(untitled) - Szejtli, J. (Chem. Rev., 1998)

(untitled) - Khan, A. R.; Forgo, P.; Stine, K. J.; D'Souza, V. T. (Chem. Rev., 1998)

(untitled) - Hedges, A. R. (Chem. Rev., 1998)

(untitled) - Leclercq, L.; Bricout, H.; Tilloy, S.; Monflier, E. (J. Colloid Interface Sci., 2007)

(untitled) - Funasaki, N.; Ishikawa, S.; Neya, S. (Pure Appl. Chem., 2008)

(untitled) - Leclercq, L.; Lacour, M.; Sanon, S. H.; Schmitzer, A. R. (Chem. – Eur. J., 2009)

(untitled) - van de Manakker, F.; Vermonden, T.; van Nostrum, C. F.; Hennink, W. E. (Biomacromolecules, 2009)

(untitled) - Denyer, S. P. (Int. Biodeterior. Biodegrad., 1995)

(untitled) - Maillard, J.-Y. (Ther. Clin. Risk Manage., 2005)

(untitled) - Rauwel, G.; Leclercq, L.; Criquelion, J.; Aubry, J.-M.; Nardello-Rataj, V. (J. Colloid Interface Sci., 2012)

(untitled) - Gilbert, P.; Pemberton, D.; Wilkinson, D. E. (J. Appl. Bacteriol., 1990)

(untitled) - Rajendran, S.; Apparao, B. V.; Palaniswamy, N. (Anti-Corros. Methods Mater., 1997)

Disinfection, Sterilization, and Preservation - Lehmann, R. H. (Synergism in Disinfectant Formulation, 2001)

(untitled) - Barney, R.; Stark, T.; Delaet, D. (Am. J. Undergrad. Res., 2006)

(untitled) - Russell, A. D. (J. Hosp. Infect., 2004)

(untitled) - Dettenkofer, M.; Wenzler, S.; Amthor, S.; Antes, G.; Motschall, E.; Daschner, F. D. (Am. J. Infect. Control, 2004)

Patch Testing Tips - Goossens, E. (Occupational Allergic Contact Dermatitis: New Facets, 2014)

(untitled) - Shaffer, M. P.; Belsito, D. V. (Contact Dermatitis, 2000)

(untitled) - De Groot, A. C.; Flyvholm, M.-A.; Lensen, G.; Menné, T.; Coenraads, P.-J. (Contact Dermatitis, 2009)

(untitled) - Waclawski, E. R.; McAlpine, L. G.; Thomson, N. C. (Br. Med. J., 1989)

(untitled) - Waran, K. D.; Munsick, R. A. (Lancet, 1995)

(untitled) - Henry, M.; Béguin, M.; Requier, F.; Rollin, O.; Odoux, J.-F.; Aupinel, P.; Aptel, J.; Tchamitchian, S.; Decourtye, A. (Science, 2012)

(untitled) - Higuchi, T.; Connors, K. A. (Adv. Anal. Chem. Instrum., 1965)

(untitled) - Martin del Valle, E. M. (Process Biochem., 2004)

(untitled) - Loftsson, T.; Hreinsdóttir, D.; Másson, M. (Int. J. Pharm., 2005)

(untitled) - Loftsson, T.; Magnúsdóttir, A.; Másson, M.; Sigurónsdóttir, J. F. (J. Pharm. Sci., 2002)

(untitled) - Leclercq, L.; Schmitzer, A. R. (Organometallics, 2010)

(untitled) - Jansook, P.; Kurov, S. V.; Loftsson, T. (J. Pharm. Sci., 2010)

(untitled) - Lezcano, M.; Al-Soufi, W.; Novo, M.; Rodriguez-Núñez, E.; Tato, J. V. (J. Agric. Food Chem., 2002)

(untitled) - Hurley, J. C.; Volz, S. A.; Johnston, J. J. (J. Agric. Food Chem., 1999)

Metabolic pathways of agrochemicals - Hutson, D. H.; Roberts, T. R.; Jewess, P. J. (Royal Society of Chemistry, 1999)

(untitled) - Garcia Reyes, J. F.; Barrales, P. O.; Diaz, A. M. (Anal. Chim. Acta, 2003)

(untitled) - Ben-Aziz, A.; Aharonson, N. (Pestic. Biochem. Physiol., 1974)

U.S. Patent - Schmidt, A.; von der Eltz, H.; Kaluza, K. (Cyclodextrin-biocide complex, 1996)

(untitled) - Ge, X.; Huang, Z.; Tian, S.; Huang, Y.; Zeng, C. (Carbohydr. Polym., 2012)

(untitled) - Lehner, S. J.; Müller, B. W.; Seydel, J. K. (Int. J. Pharm., 1993)

(untitled) - Uekama, K.; Ikeda, Y.; Hirayama, F.; Otagiri, M.; Shibata, M. (Yakugaku Zasshi, 1980)

(untitled) - Lehner, S. J.; Müller, B. W.; Seydel, J. K. (J. Pharm. Pharmacol., 1994)

U.S. Patent - Szejtli, J.; Tétényi, P.; Kiniczky, M.; Bernáth, J.; Tetenyi-Erdösi, M.; Dobos, E.; Banky-Elöd, E. (Process for enhancing the activity of plant protecting agents by using cyclodextrin, 1990)

(untitled) - Singh, R. P.; Brindle, I. D.; Hall, C. D.; Chiba, M. (J. Agric. Food Chem., 1990)

(untitled) - Schirra, M.; Delogu, G.; Cabras, P.; Angioni, A.; D’halleiwin, G.; Veyrat, A.; Marcos, J. F.; González Candelas, L. (J. Agric. Food Chem., 2002)

Chin. Patent - Zhang, A.; Zhou, S.; Liu, W. (Clathrate of chloramine phosphate and cyclodextrin or its derivative and the preparation process, 2007)

(untitled) - Zhou, S.; Wang, L.; Zhang, A.; Lin, K.; Liu, W. (J. Agric. Food Chem., 2008)

(untitled) - Hill, L. E.; Gomes, C.; Taylor, T. M. (LWT–Food Sci. Technol., 2013)

(untitled) - Bustamante, M.; Durán, N.; Diez, M. C. (J. Soil Sci. Plant Nutr., 2012)

(untitled) - Van Hamme, J. D.; Singh, A.; Ward, O. P. (Biotechnol. Adv., 2006)

(untitled) - Singh, A.; Van Hamme, J. D.; Ward, O. P. (Biotechnol. Adv., 2007)

(untitled) - Wang, X.; Brusseau, M. L. (Environ. Sci. Technol., 1995)

(untitled) - Wang, J.-M.; Marlowe, E. M.; Miller-Maier, R. M.; Brusseau, M. L. (Environ. Sci. Technol., 1998)

(untitled) - Boyle, D. (J. Environ. Manage., 2006)

(untitled) - Loukas, Y. L.; Antoniadou-Vyza, E.; Papadaki-Valiraki, A.; Machera, K. G. (J. Agric. Food Chem., 1994)

(untitled) - Alonso, M. L.; Recio, G.; Alonso, R. M.; Jiménez, R. M.; Laza, J. M.; Vilas, J. L.; Fañanás, R. (Int. J. Environ. Anal. Chem., 2012)

(untitled) - Cireli, A.; Yurdakul, B. (J. Appl. Polym. Sci., 2006)

(untitled) - Buschmann, H.-J.; Knittel, D.; Schollmeyer, E. (J. Inclusion Phenom. Macrocyclic Chem., 2001)

(untitled) - Loftsson, T.; Duchêne, D. (Int. J. Pharm., 2007)

(untitled) - Wang, J.-h.; Cai, Z. (Carbohydr. Polym., 2008)

(untitled) - Qian, L.; Guan, Y.; Ziaee, Z.; He, B.; Zheng, A.; Xiao, H. (Cellulose, 2009)

(untitled) - Dong, C.; Ye, Y.; Qian, L.; Zhao, G.; He, B.; Xiao, H. (Cellulose, 2014)

(untitled) - Podolak, M.; Man, D.; Waga, S.; Przestalski, S. (Z. Naturforsch., C, 1996)

(untitled) - Balgavý, P.; Devínsky, F. (Adv. Colloid Interface Sci., 1996)

(untitled) - Schlieper, P.; De Roberts, E. (Arch. Biochem. Biophys., 1977)

(untitled) - Groot, R. D.; Rabone, K. L. (Biophys. J., 2001)

(untitled) - Simpson, W. J. (FEMS Microbiol. Lett., 1992)

(untitled) - Loftsson, T.; Stefánsdóttir, O.; Friôriksdóttir, H.; Guômundsson, Ö. (Drug Dev. Ind. Pharm., 1992)

(untitled) - Malaekeh-Nikouei, B.; Bazzaz, B. S. F.; Soheili, V.; Mohammadian, K. (Jundishapur J. Microbiol., 2013)

(untitled) - Leclercq, L.; Nardello-Rataj, V.; Rauwel, G.; Aubry, J.-M. (Eur. J. Pharm. Sci., 2010)

(untitled) - Leclercq, L.; Lubart, Q.; Dewilde, A.; Aubry, J.-M.; Nardello-Rataj, V. (Eur. J. Pharm. Sci., 2012)

(untitled) - Fauvelle, F.; Debouzy, J. C.; Crouzy, S.; Göschl, M.; Chapron, Y. (J. Pharm. Sci., 1997)

(untitled) - Debouzy, J. C.; Fauvelle, F.; Crouzy, S.; Girault, L.; Chapron, Y.; Göschil, M.; Gadelle, A. (J. Pharm. Sci., 1998)

(untitled) - Leclercq, L.; Lubart, Q.; Aubry, J.-M.; Nardello-Rataj, V. (Langmuir, 2013)

(untitled) - Concheiro, A.; Alvarez-Lorenzo, C. (Adv. Drug Delivery Rev., 2013)

(untitled) - Garcia-Fernandez, M. J.; Brackman, G.; Coenye, T.; Concheiro, A.; Alvarez-Lorenzo, C. (Biofouling, 2013)

(untitled) - Stobie, N.; Duffy, B.; McCormack, D. E.; Colreavy, J.; Hidalgo, M.; McHale, P.; Hinder, S. J. (Biomaterials, 2008)

(untitled) - Feng, Q. L.; Wu, J.; Chen, G. Q.; Cui, F. Z.; Kim, T. N.; Kim, J. O. (J. Biomed. Mater. Res., 2000)

(untitled) - He, B.; Tan, J. J.; Liew, K. Y.; Liu, H. (J. Mol. Catal. A: Chem., 2004)

(untitled) - Kochkar, H.; Aouine, M.; Ghorbel, A.; Berhault, G. (J. Phys. Chem. C, 2011)

(untitled) - Jaiswal, S.; Duffy, B.; Jaiswal, A. K.; Stobie, N.; McHale, P. (Int. J. Antimicrob. Agents, 2010)

(untitled) - George, C.; Kuriakose, S.; Prakashkumar, B.; Mathew, T. (Supramol. Chem., 2010)

(untitled) - George, C.; Kuriakose, S.; George, S.; Mathew, T. (Supramol. Chem., 2011)

(untitled) - Priya, R. S.; Geetha, D.; Ramesh, P. S. (Carbon: Sci. Technol., 2013)

(untitled) - Bajpai, M.; Gupta, P.; Bajpai, S. K. (Fibers Polym., 2010)

(untitled) - Popescu, O.; Dunca, S.; Grigoriu, A. (Cellul. Chem. Technol., 2013)

(untitled) - Andrade, P. F.; de Faria, A. F.; da Silva, D. S.; Bonacin, J. A.; do Carmo Gonçalves, M. (Colloids Surf., B, 2014)

(untitled) - Stanier, C. A.; O'Connell, M. J.; Clegg, W.; Anderson, H. L. (Chem. Commun., 2001)

(untitled) - Stoimenov, P. K.; Klinger, R. L.; Marchin, G. L.; Klabunde, K. J. (Langmuir, 2002)

(untitled) - Lukhele, L. P.; Krause, R. W. M.; Nhlabatsi, Z. P.; Mamba, B. B.; Momba, M. N. B. (Desalin. Water Treat., 2011)

(untitled) - Liu, S.; Wei, L.; Hao, L.; Fang, N.; Chang, M. W.; Xu, R.; Yang, Y.; Chen, Y. (ACS Nano, 2009)

(untitled) - Arias, L. R.; Yang, L. (Langmuir, 2009)

(untitled) - Selvam, S.; Gandhi, R. R.; Suresh, J.; Gowri, S.; Ravikumar, S.; Sundrarajan, M. (Int. J. Pharm., 2012)

(untitled) - Li, H.; Li, C.; Zhang, C.; Bai, J.; Xu, T.; Sun, W. (J. Appl. Polym. Sci., 2014)

(untitled) - Duca, G.; Ivancic, A.; Boldescu, V. (Chem. J. Mold., 2012)

(untitled) - Miyazawa, I.; Ueda, H.; Nagase, H.; Endo, T.; Kobayashi, S.; Nagai, T. (Eur. J. Pharm. Sci., 1995)

(untitled) - Irie, T.; Uekama, K. (J. Pharm. Sci., 1997)

(untitled) - Kilsdonk, E. P. C.; Yancey, P. G.; Stoudt, G. W.; Bangerter, F. W.; Johnson, W. J.; Phillips, M. C.; Rothblat, G. H. (J. Biol. Chem., 1995)

(untitled) - Ohtani, Y.; Irie, T.; Uekama, K.; Fukunaga, K.; Pitha, J. (Eur. J. Biochem., 1989)

(untitled) - Danthi, P.; Chow, M. (J. Virol., 2004)

(untitled) - Wielgosz, M. M.; Rauch, D. A.; Jones, K. S.; Ruscetti, F. W.; Ratner, L. (AIDS Res. Hum. Retroviruses, 2005)

(untitled) - Hambleton, S.; Steinberg, S. P.; Gershon, M. D.; Gershon, A. A. (J. Virol., 2007)

(untitled) - Bremer, C. M.; Bung, C.; Kott, N.; Hardt, M.; Glebe, D. (Cell. Microbiol., 2009)

(untitled) - Liao, Z.; Graham, D. R.; Hildreth, J. E. K. (AIDS Res. Hum. Retroviruses, 2003)

(untitled) - Leydet, A.; Moullet, C.; Roque, J.-P.; Witvrouw, M.; Pannecouque, C.; Andrei, G.; Snoeck, R.; Neyts, J.; Schols, D.; de Clercq, E. (J. Med. Chem., 1998)

(untitled) - Liao, Z.; Cimakasky, L. M.; Hampton, R.; Nguyen, D. H.; Hildreth, J. E. K. (AIDS Res. Hum. Retroviruses, 2001)

U.S. Patent - Carlson, R. M.; Froberg, M. K.; Khan, M. A.; Rice, S. A.; Wallace, K. B. (Cyclodextrin compositions and methods of treating viral infections, 2003)

(untitled) - Crandall, I. E.; Szarek, W. A.; Vlahakis, J. Z.; Xu, Y.; Vohra, R.; Sui, J.; Kisilevsky, R. (Biochem. Pharmacol., 2007)

(untitled) - Lin, C.-D.; Lai, C.-K.; Lin, Y.-H.; Hsieh, J.-T.; Sing, Y.-T.; Chang, Y.-C.; Chen, K.-C.; Wang, W.-C.; Su, H.-L.; Lai, C.-H. (Infect. Immun., 2011)

(untitled) - Pucadyil, T. J.; Tewary, P.; Madhubala, R.; Chattopadhyay, A. (Mol. Biochem. Parasitol., 2004)

(untitled) - Zhang, H.-M.; Li, Z.; Uematsu, K.; Kobayashi, T.; Horikoshi, K. (Arch. Microbiol., 2008)

(untitled) - Boldescu, V.; Macaev, F.; Duca, G. (Chem. J. Mold., 2014)

(untitled) - Macaev, F.; Boldescu, V.; Geronikaki, A.; Sucman, N. (Curr. Top. Med. Chem., 2013)

(untitled) - Brzostek, A.; Pawelczyk, J.; Rumijowska-Galewicz, A.; Dziadek, B.; Dziadek, J. (J. Bacteriol., 2009)